2010
DOI: 10.1016/j.phymed.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic effect of siphonaxanthin from green alga, Codium fragile

Abstract: Since anti-angiogenic therapy has becoming a promising approach in the prevention of cancer and related diseases, the present study was aimed to examine the anti-angiogenic effect of siphonaxanthin from green alga (Codium fragile) in cell culture model systems and ex vivo approaches using human umbilical vein endothelial cells (HUVECs) and rat aortic ring, respectively. Siphonaxanthin significantly suppressed HUVEC proliferation (p<0.05) at the concentration of 2.5 μM (50% as compared with control) and above, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 44 publications
0
61
0
Order By: Relevance
“…Their results showed that Sargassum seaweed extract can reduce the length and number of blood vessels in the CAM model [12]. Also Ganesan et al showed that the siphonaxanthin is derived from green algae can inhibit angiogenesis in ex vivo and in vitro [13].…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that Sargassum seaweed extract can reduce the length and number of blood vessels in the CAM model [12]. Also Ganesan et al showed that the siphonaxanthin is derived from green algae can inhibit angiogenesis in ex vivo and in vitro [13].…”
Section: Discussionmentioning
confidence: 99%
“…The generation and analysis of transgenic and knockout mice for MMPs have confirmed that MMPs play key roles in the process of carcinogenesis and invasion (21). One of these, MMP-9, is regarded as a critical molecule in tumor progression and invasion (22). Therefore, inhibition of MMP-9 appears to be an ideal strategy to control tumor growth, invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…21,22) HUVECs were plated onto 96-well plates (1.5×10 3 cells/well) and incubated for 24 h at 37°C in 5% CO 2 . The medium was removed and replaced with fresh HuMedia EG2 containing various doses of compound or vehicle (DMSO) and incubated for 72 h under the same condition.…”
Section: Huvec Proliferation Assaymentioning
confidence: 99%
“…21,22) Solid gel was prepared on a 96-well tissue culture plate according to the manufacture's instruction. HUVECs (1×10 5 cells/mL) in HuMedia EG2 medium containing various doses of compound or vehicle (DMSO) (100 µL) were seeded onto the surface on BD Matrigel.…”
Section: Huvec Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation